2018
DOI: 10.1016/j.cmet.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The Homeostatic Force of Ghrelin

Abstract: Ghrelin, a gastric-derived acylated peptide, regulates energy homeostasis by transmitting information about peripheral nutritional status to the brain, and is essential for protecting organisms against famine. Ghrelin operates brain circuits to regulate homeostatic and hedonic feeding. Recent research advances have shed new light on ghrelin's multifaceted roles in cellular homeostasis, which could maintain the internal environment and overcome metaflammation in metabolic organs. Here, we highlight our current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
240
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 244 publications
(248 citation statements)
references
References 247 publications
3
240
0
5
Order By: Relevance
“…In summary, in the present study, we found that central administration of the GHSR antagonist [D-Lys3]-GHRP-6 or JMV2959 did not affect HF intake escalation over the successive days or cumulative 4-day HF intake, supporting the notion that circulating ghrelin does not affect brain areas regulating binge-like HF intake. By contrast, i.c.v.-injected K-(D-1-Nal)-FwLL-NH 2 reduced daily HF intake, HF intake escalation over the successive days and cumulative 4-day HF intake, in a similar fashion to that seen for i.c.v.-injected LEAP2 [1][2][3][4][5][6][7][8][9][10][11][12][13][14] . Notably, central administration of these GHSR synthetic ligands did not affect 22hour food intake and body weight.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…In summary, in the present study, we found that central administration of the GHSR antagonist [D-Lys3]-GHRP-6 or JMV2959 did not affect HF intake escalation over the successive days or cumulative 4-day HF intake, supporting the notion that circulating ghrelin does not affect brain areas regulating binge-like HF intake. By contrast, i.c.v.-injected K-(D-1-Nal)-FwLL-NH 2 reduced daily HF intake, HF intake escalation over the successive days and cumulative 4-day HF intake, in a similar fashion to that seen for i.c.v.-injected LEAP2 [1][2][3][4][5][6][7][8][9][10][11][12][13][14] . Notably, central administration of these GHSR synthetic ligands did not affect 22hour food intake and body weight.…”
Section: Discussionmentioning
confidence: 70%
“…43 Because we recently demonstrated that the N-terminal sequence of LEAP2 confers full receptor binding and activity, 7 a peptide containing the initial 14 residues of N-terminal LEAP2 sequence (hereafter named LEAP2 1-14 ) was employed as an analogue of full-length LEAP2. LEAP2 [1][2][3][4][5][6][7][8][9][10][11][12][13][14] was assembled on solid support using Fmoc chemistry and starting from Amphisphere 40 RAM resin (Agilent Technologies Inc., Santa Clara, CA, USA), purified by reverse phase-high-performance liquid chromatography and characterised by liquid chromatography-mass spectrometry and matrix-assisted laser desorption/ionization-tandem mass spectrometry with a purity > 95%, as described previously. 7 LEAP2 1-14 was dissolved in PBS.…”
Section: Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…Univariate and multivariate analyses of prognostic factors (n=69). injury and promotes muscle regeneration and inhibit apoptosis in myoblasts cocultured with colon carcinoma cells (37,38). Specific receptors of DG that promote these activities have not been identified, and a feedback mechanism such as that with AG is unknown.…”
Section: Univariate Multivariate ------------------------------------mentioning
confidence: 99%